EMPIRICAL STUDY OF THE PERCEPTION OF THE IMAGE OF THE FUTURE PROFESSION BY PSYCHOLOGY STUDENTS (Psychology Travelogs, 2024)
The article presents the results of an empirical study of the perception of the image of the future profession by psychology students. Such diagnostic tools were used in the research: the quastionary of professional concept of future profession (by D. Vetocha, L. Podkorytova, modification by A. Nikityuk; the «Twenty Statements» method or «Who am I?» (M. Kuhn and T. McPartland); the «Differential Diagnostic Questionnaire» method, the «Professional Identity Status» Questionnaire (O. Radzimovska), the Professional Orientation Questionnaire (OPS) (D. Holand).The results obtained by different methods agree with each other. In particular, according to both the differential diagnostic questionnaire (DDO) and the occupational orientation questionnaire (OPS) (D. Holand), the vast majority of the studied psychology students belong to the types of professions to which a psychologist corresponds («person-person» type according to the DDO and social type according to OPS).The coincidence of answers according to the «Twenty statements» methods is also noted. (M. Kuhn and T. McPartland) and the «Professional Identity Status» questionnaire: most of the studied psychology students showed a fairly high level of self-identification with their future profession. At the same time, there are some students who have a low level of professional identity, do not identify with their future profession and have not very realistic ideas about what they will do in the future.Summarizing the results of five studies, we can say that the choice of a profession should be subject to the conscious need to reconcile the aspirations and intentions of the individual, as well as the correlation of one's own qualities with the requirements set forth by each profession, then students will be less disappointed. For this, it is necessary to study in detail all the intricacies of the chosen field of activity, what image a specialist in this or that field represents, because this determines the further attitude to possible ups and downs in a professional career.We associate the prospects for further research on the peculiarities of the perception of the image of the future profession by psychology students with the study of the influence of new forms and methods on the formation of the professional orientation of future psychologists and, first of all, with the spread and improvement of forms and methods of practical training of professional psychologists, the approval of developed recommendations and training.
Keywords: perception; image of the profession; formation of the image of the profession; profession «psychologist»; student